Management Strategies to Achieve Operational Excellence for Startup Business in the Digital Age - Pongkronkumpol, Poramets; Sawatenarakul, Natha; Silpcharu, Thanin (Migration Letters, 2023)
Thailand has potential in digital technology. Therefore, we changed to a new type of business that emphasizes innovation and technology. Make startups have high potential. This research aims to study management strategies for excellence in startup businesses in the digital era. The population used in this research is a group of entrepreneurs with management strategies for excellence in startup businesses in the digital era that have been selected to enter the Thai startup business sector. (Ministry of Science and Technology, 2022) and then developed into a structural equation model. Conduct both qualitative and quantitative research. Explore quantitative data from interviews with 500 start-up businesses, which used both descriptive statistics, reference statistics, and multiple statistics to analyze the data. The results showed that the guidelines for Management Strategies to Achieve Operational Excellence for Startup Business in the Digital Age of 4 aspects. The most important factors of each aspect are as following: 1) Blue Ocean focus aspects (X ̅ = 4.75) which its most important factor is Prepared to explore new business opportunities by connecting with the existing business to retain the old customer base 2) Alliances Centric aspects (X ̅ = 4.62) which its most important factor is Establishing goals and objectives for collaborative business operations between partners for efficient management 3) Innovation environment aspects (X ̅ = 4.60) which its most important factor is Overseeing the security responsibilities of the organization’s information technology systems, risk prevention, and fostering awareness of various risks within the organization’s information technology systems 4) Transformational Leaders aspects (X ̅ = 4.59) which its most important factor is Digital leaders must find ways to promote the achievements of startups to be recognized in the target market. For the hypothesis test showed that no statistically significant difference in Business organization type at the level of 0.05. The analysis of the developed structural equation model showed that it was in accordance and harmony with the empirical data and passed the evaluation criteria. Its Chi-square probability level, relative Chi-square, the goodness of fit index, and root mean square error of approximation were 0.114, 1.075, 0.938, and 0.012, respectively. The statistical significance of this study was set at 0.05.